Rasionalisme dan Empirisme Dalam Filsafat Ontologi - Muhamad Agus Nurohman (Jurnal Dewantara, 2020)
The discussion of ontology in this article concentrates on the of "being essential" whose application leads to three main discussions, namely: the essention of science, the law of causality and the potentials. First, the essence of "being" is the integration among the essence of science and the systematically formed physical universe (cosmos). Second, the law of causality is absolutly which is immune from any deviation as in the understanding of causal determinism/ absolute causalism. On the other hand it is maintaining the nature principle and its phenomenas are governed by God. Third, human being is develop creature because they are influenced by nature and society. In its development, human tends to be religious. This tendency can be divided into two things, namely the tendency to be a good person and the tendency to be a bad person. Religious tendency is the tendency to be good.